2008
DOI: 10.1017/s1743921308022710
|View full text |Cite
|
Sign up to set email alerts
|

Deep inside low-mass stars

Abstract: Abstract. Low-mass stars exhibit, at all stages of their evolution, the signatures of complex physical processes that require challenging modeling beyond standard stellar theory. In this review, we recall the most striking observational evidences that probe the interaction and interdependence of various transport processes of chemicals and angular momentum in these objects. We then focus on the impact of atomic diffusion, large scale mixing due to rotation, and internal gravity waves on stellar properties on t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 62 publications
(68 reference statements)
1
10
0
Order By: Relevance
“…Charbonnel & Primas suggested that such a behaviour may be the signature of a transport process of chemical elements and angular momentum whose efficiency changes on the blue edge of the plateau. This behaviour corresponds to that of the generation and filtering of internal gravity waves in both Population II and I stars (Talon & Charbonnel 2003;Charbonnel & Talon 2008). Talon & Charbonnel (2004) describe how internal gravity waves coupled with rotation-induced mixing are expected to lead to higher Li homogeneity among the plateau dwarf stars than among the more massive, slightly evolved stars, a scenario which may explain the observational findings by Charbonnel & Primas. Speaking in favour of this model is its ability to simultaneously explain the internal solar rotation profile and the time evolution of the Li abundance at the surface of solar-and F-type stars as seen in Galactic open clusters (Charbonnel & Talon 2005).…”
Section: Introductionsupporting
confidence: 62%
“…Charbonnel & Primas suggested that such a behaviour may be the signature of a transport process of chemical elements and angular momentum whose efficiency changes on the blue edge of the plateau. This behaviour corresponds to that of the generation and filtering of internal gravity waves in both Population II and I stars (Talon & Charbonnel 2003;Charbonnel & Talon 2008). Talon & Charbonnel (2004) describe how internal gravity waves coupled with rotation-induced mixing are expected to lead to higher Li homogeneity among the plateau dwarf stars than among the more massive, slightly evolved stars, a scenario which may explain the observational findings by Charbonnel & Primas. Speaking in favour of this model is its ability to simultaneously explain the internal solar rotation profile and the time evolution of the Li abundance at the surface of solar-and F-type stars as seen in Galactic open clusters (Charbonnel & Talon 2005).…”
Section: Introductionsupporting
confidence: 62%
“…These models were found to explain the corresponding Li data for both main sequence and giant stars in the intermediate-age IC 4651 (see Pasquini et al 2004), as they do for younger clusters like the Hyades, Coma Berenices, and Praesepe (see e.g. Charbonnel & Talon 2008).…”
Section: Comparison With Model Predictions For Rotating Starsmentioning
confidence: 61%
“…The internal dynamics of these stars is altered by the effects of rotation, through the transport of both angular momentum and chemical species and through the action of meridional circulation and shear turbulence, combined possibly with other processes induced by internal gravity waves or magnetic fields (e.g. Zahn 1992;Maeder & ZahnA&A 580, A141 (2015) beginning of the RGB, successfully explaining many abundance patterns observed at the surface of low-and intermediate-mass stars (Palacios et al 2003;Charbonnel & Talon 2008;Smiljanic et al 2010;. Rotation has also been investigated by several authors as a possible source of mixing during the RGB to explain abundance anomalies observed at the surface of RGB stars (e.g.…”
Section: Introductionmentioning
confidence: 95%